2(x-3)-(4x+1)(4x-1)

2(x-3)-(4x+1)(4x-1) = 2x-6-(14x^2-4x+4x-1) = 2x-6-14x^2+1 = -14x^2+2x-5

Using quadratic formula: a=-14; b=2; c=-5

(-b+/- sqrt(b^2-4*a*c))/(2a) = (-2+/-sqrt(4-4*(-14)(-5))/(-28) = (-2+/-sqrt(-276))/-28

(-2+2*i*sqrt(69))/(-28) = (1-i*sqrt(69))/14; ---or---; (-2-2*i*sqrt(69))/(-28) = (1+i*sqrt(69))/14

Two imaginary roots as noted above.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up